Craft and Automation. Issue 5 (20th October 2021) - Andrews, Chris
Abstract: How far has the Oulipo gone in the directions of conceptual writing and automation? Conceptualism is built into the very idea of potential literature, but the group's interest in automation has gradually waned. Computer-assisted literary composition was delegated to an offshoot workshop (the Alamo), which has not thrived. If the Oulipo's activity is essentially craftlike, as Jacques Roubaud has written, this is not surprising. Nevertheless, some of the group's members have used their craft to imagine or simulate automation. Georges Perec and Marcel Benabou's P.A.L.F. ("Production automatique de littérature française") project, and Perec's radio play Die Maschine illustrate this strategy.